THE BATTLE OF KOŠARE 25 YEARS LATER: MEDIA AND POLITICAL NARRATIVES - Jelena; Pešić, Milena (The Policy of National Security, 2025)
The Battle of Košare was fought in the border area between the Federal Republic of Yugoslavia and Albania. It began on April 9, 1999, and lasted 67 days. Although many young lives were lost in this battle, it was precisely this battle that prevented the deeper penetration of the terrorist KLA, supported by the regular Albanian army and NATO, into Kosovo and Metohija. However, as is often the case, military events are one thing, the political implications are another, and the media and political narratives surrounding the events themselves are yet another. “The Heavenly Guard of Free Serbia” or “sacrificed youth”, a feat that is remembered or a battle that is not mentioned so as not to offend foreign “partners”? The aim of this paper is precisely to investigate how the media and political elites in Serbia see the Battle of Košare 25 years later. In this sense, we will analyze the content of television news programs and other special programs (if any), online media reports, as well as media statements and social media pages of political parties and actors in Serbia during the period when the 25th anniversary of the Battle of Košare was commemorated. With this analysis, we will try to determine whether and within which narratives the media and political elites commemorated this anniversary and spoke (or did not speak) about the battle itself and its implications, and whether there are differences between different media and different political actors in this sense, and what we can conclude from these differences.
Keywords: Battle of Košare; media narratives; political discourse; culture of remembrance; nation brand; communication; media content analysis